Influence of Negative Skin Friction Phenomenon on Reinforced Concrete Pile Design - Le , Phương; Truong , Anh Tuấn; Dao , Nguyên An (Journal of Technical Education Science, 2021)
Since negative skin friction was known in pile foundation’s behaviour, there have been many research and science reports on this problem in the world, in order to discover the essence and value of negative skin friction in foundation’s development stages. Namely, the reconsolidation of highly sensitive soils due to pile installation (Fellenious 1972), recent embankment fill (Bozozuk 1972), water table fluctuation (Auvinet and Hanell 1981). In our country, nowadays, negative skin friction is getting more attention in design and construction work of deep foundation, especially in the soft soil area, such as in District 7 – HCM City. Based on gathering documents, studying the calculation theory of Dr. Joseph E. Bolwes and setting up the calculated model on Plaxis, with the real geologic of District 7 – HCM City, we demonstrated and showed the influence of negative skin friction on pile in this area, and found out some solutions to this problem.